Reconceptualizing Student Engagement: Investigating the Validity of CCSSE Benchmarks as Indicators of International Student Engagement - Ghazzawi, Dina; McKinney, Lyle; Horn, Catherine; Backsheider Burridge, Andrea; Carales, Vincent (Journal of International Students, 2021)
International students in the United States have been increasingly attracted to community colleges as a starting point to higher education. Recently, their enrollment has been dropping. Research highlights the importance of student engagement to international students. However, few studies investigate their engagement experiences in community colleges. This study investigated the validity of the Community College Survey of Student Engagement (CCSSE) benchmarks as proxies for international student engagement in community colleges. The original CCSSE benchmarks were a poor fit for international students. Resulting constructs and underlying items differed significantly from the original benchmarks and demonstrated poor reliability. Findings highlight the inapplicability of CCSSE benchmarks in representing international student engagement. Recommendations include adding culturally relevant variables to the CCSSE structure more applicable to international student populations, and accompanying the survey with qualitative input for in-depth knowledge of international student experiences.